The OLI Model and LLL Model in Internationalization Process: Perspectives from Foreign Direst Investment with Chinese Internet Companies - Wang, Lin (2015)
This paper aims to be able to make an empirical assessment of two analytical frameworks; the Eclectic Production Paradigm (Dunning, 2000), the ownership–location–internalisation (OLI) Model, and the linkage–leverage–learning (LLL) Model of MNE formation, as defined by Mathews (2006). It will take into account the market experiences, in the pursuit of internationalisation, which Chinese internet enterprises have undergone. The paper will begin with a brief characterisation of emerging market enterprises with FDI. It will highlight the way in which the two approaches describe and define internationalisation processes. A research instrument was prepared which can be used to make a comparative analysis of internationalisation, as dictated by the aforementioned approaches. The evidence from three Chinese case studies suggests that the traditional OLI and the newly proposed linkage–leverage–learning (LLL) Model of MNE formation can be treated as complementary to one another. Yet, it also opens up questions about the development of an integrative framework, with the aim of improving understanding of emerging market enterprises across the international stage.